"Tibet, fifty years after" - "Dewan, Parvez" (Gurgaon, 2009)
Two Indians-the first Tibet ologists from Gyagar sinces Rahuul Sankrityayan (1893-1963) went to Tibet to plug gaps in their knowledge of Himalayan Buddhism, and to see how Tibet compared with the neighbouring Ladakh region of India. What they found instead was an affluent, breathtakingly planned, 21st century town. With sparking six-lance roads and glass front shops that sold all the top international designer labels.
Keywords: Tibet Autonomous Region (China) - Description and travel